Plasticity and lineage commitment of individual TH1 cells are determined by stable T-bet expression quantities - Hegazy, Ahmed Nabil; Peine, Caroline; Niesen, Dominik; Panse, Isabel; Vainshtein, Yevhen; Kommer, Christoph; Zhang, Qin; Brunner, Tobias M.; Peine, Michael; Fröhlich, Anja; Ishaque, Naveed; Marek, Roman M.; et al. (Science advances, 2024)
T helper 1 (TH1) cell identity is defined by the expression of the lineage-specifying transcription factor T-bet. Here, we examine the influence of T-bet expression heterogeneity on subset plasticity by leveraging cell sorting of distinct in vivo-differentiated TH1 cells based on their quantitative expression of T-bet and interferon-γ. Heterogeneous T-bet expression states were regulated by virus-induced type I interferons and were stably maintained even after secondary viral infection. Exposed to alternative differentiation signals, the sorted subpopulations exhibited graded levels of plasticity, particularly toward the TH2 lineage: T-bet quantities were inversely correlated with the ability to express the TH2 lineage-specifying transcription factor GATA-3 and TH2 cytokines. Reprogramed TH1 cells acquired graded mixed TH1 + TH2 phenotypes with a hybrid epigenetic landscape. Continuous presence of T-bet in differentiated TH1 cells was essential to ensure TH1 cell stability. Thus, innate cytokine signals regulate TH1 cell plasticity via an individual cell-intrinsic rheostat to enable T cell subset adaptation to subsequent challenges.
Gesehen am 14.02.2025
Im Titel ist "H" tiefgestellt